Collagenous spherulosis in an adenomyoepithelioma of the breast. Issue 1 (23rd December 2003) - Reis-Filho, J S; Fulford, L G; Crebassa, B; Carpentier, S; Lakhani, S R
Abstract : Collagenous spherulosis (CS) is an incidental finding that usually occurs in association with benign proliferative and preinvasive lesions. Adenomyoepithelioma is a biphasic neoplasm of the breast, composed of both luminal epithelial and myoepithelial cells. Despite the common epimyoepithelial histogenesis, CS has never been described in association with adenomyoepithelioma. This report describes the case of a 48 year old woman who presented with CS of the breast in an adenomyoepithelioma. The combination of these two benign lesions led to diagnostic difficulties; namely, differentiation from adenoid cystic carcinoma, but also cribriform carcinoma and cylindroma of the breast. Antibodies to the oestrogen receptor, progesterone receptor, p63, and c-kit (CD117) proved to be useful adjuncts to differentiate between these lesions.